Use of ballasted flocculation (BF) sludge for the manufacturing of lightweight aggregates. (1st March 2022) - Lee, Kang Hoon; Qasim, Muhammad; Lee, Ki Gang; Inam, Muhammad Ali; Khan, Imtiaz Afzal; Khan, Rizwan; Wie, Young Min
Abstract: Ballasted flocculation (BF) is an efficient way to remove the turbidity from surface water. The objective of the present study is to optimize the ballast (magnetite), coagulant (poly aluminum chloride) concentration and pH for efficient turbidity removal from surface water. To do this, the sludge produced from an optimized dose of a BF treatment was utilized for the production of lightweight (LW) aggregates by combining it with hard clay and sewage sludge. The LW aggregates were formed by means of rapid sintering in the temperature range of 1000–1200 °C with an exposure time of 10 min. The physical properties of the LW aggregates, in this case the leaching of heavy metals, the bulk density and the microstructure, were investigated. The results indicated that corresponding ballast and coagulant concentrations of 0.75 g/L and 30 mg/L (poly aluminum chloride (PAC)) resulted in the maximum removal efficiency of ≈95%. Using a mixture of BF sludge (30 wt%), dry sewage sludge (20 wt%), and hard clay (50 wt%), aggregates with a density of around 1.0 g/cm 3 could be produced. In addition, it was confirmed that the manufactured aggregate was environmentally stable as the elution of heavy metals was suppressed. Graphical abstract: Image 1 Highlights: BF 30 formulation followed the Riley's criteria of LW aggregates manufacturing. Optimal coagulation conditions were achieved by using PAC and Fe3 O4 in BF process. LW aggregate with BF 30 can be manufactured with a density of less than 1.0g/㎤. Leaching of heavy metal was suppressed effectively in BF 30 aggregates.